Content analysing multi-level authority and cultural identity claims: a complement to the Comparative Manifestos Project (CMP) exemplified for Spanish regional manifestos - Volkens, Andrea; Alonso, Sonia; Gómez, Braulio (2009)
Abstract: "This handbook describes a specific approach to content analyzing multilevel party manifestos, building on a methodology that was originally developed in the context of the Manifesto Research Group (MRG). Since 1979, the MRG has been collecting and coding election programs with the aim of estimating policy preferences of political parties. The second phase of the project started in 1989. In the context of its 'Comparative Manifestos Project' (CMP), the Social Science Research Center Berlin (WZB) provided resources for updating and expanding the MRG data. Since then, country experts were hired to collect and code national election programs according to a handbook that describes how to identify the coding units and how to apply the classification scheme of policy preferences under central supervision. The CMP is solely concerned with national election programs. However, in decentralized political systems, parties also publish local and regional election programs and, in times of glob